IMPLEMENTATION LEVEL ANALYSIS OF GREENSHIP NEIGHBORHOOD ON RESORT RIAHI, NIRUP ISLAND, BATAM - Gustiabani, Zures; Alfandi, Hari; Ardi, Nadia Khaira (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
The Greenship assessment tool could be one of the criteria which could be applied to green building. Green Building Council Indonesia (GBCI) as a green concept certification body in Indonesia had published a green concept assessment tool for the area called Greenship Neighborhood Version 1.0. With this, research was done to collect the points to get the ranking in Greenship Area for Hotel and Resort Area in Nirup Island. Nirup Island which was located in Sekanak Raya, Belakang Padang Batam was a new resort area. The study was to identify Greenship Neighborhood implementation in Riahi Resort Nirup Island and to calculate the result of feasibility assessment and success rate on Nirup Island Area of Greenship implementation. The methods used to evalute the issue were observation and interview in Nirup Island, analyze and processing the data, and documentations studies. The result of the study show that the Nirup Island Area was in Gold Category which had point 72 from 122 points. It had the point from every assessment which were 12 points in Land Ecological Enchancement, 23 points in Movement and Connectivity, 13 points in Water Management and Conservation, 4 point in Solid Waste and Material, 8 points in Community Wellbeing Strategy, 10 points in Building and Energy, and 2 points in Innovation and Future Development. With the highest point were getting from Movement and Connectivity (MAC) which was 23 points or 17.7 % and the lowest in Innovation and Future Development (IFD) which was 2 points or 1.6 %.